Structure sensitive chemical reactivity by palladium concave nanocubes and nanoflowers synthesised by a seed mediated procedure in aqueous medium - Sreedhal, S.; Sudheeshkumar, V.; Vinod, C. P. (Nanoscale, 2014)
Palladium nanocubes and their transformation to concave nanocubes and nanoflowers are realised by a seed mediated procedure in aqueous medium and at room temperature using cationic surfactants. The concave nanocubes and nanoflowers were found to be enclosed by high index facets. The under coordinated atoms present on the high index facets make these nanostructures chemically more active towards Suzuki coupling and Heck coupling reactions compared to the conventional nanocubes and spherical nanoparticles of similar size.

Oxidation catalysis by large trisoctahedral gold nanoparticles: Mind the step! - Sreedhala, S.; Sudheeshkumar, V.; Vinod, C. P. (Catalysis Today, 2015)
To understand the origin of catalysis by gold and to probe the role of defects and interfaces, benchmark reactions namely CO oxidation and benzyl alcohol oxidation were carried out on supported trisoctahedral gold nanoparticles and on the inverse catalyst system. The sizes of these particles which are between 45 nm and 110 nm, are well beyond the quantum size regime and well above the optimum size range where gold is considered to be catalytically active. The periodic steps sites in contact with oxide support interface were able to promote the reaction. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: CO oxidation; Defects; Gold catalysis; Inverse catalysta; Steps and kinks

CO oxidation on large high-index faceted Pd nanostructures - Sreedhala, S.; Sudheeshkumar, V.; Vinod, C. P. (Journal of Catalysis, 2016)
The structure sensitivity of CO oxidation has been investigated on oxide-supported palladium nanoparticles of different morphologies. The reactivity of concave nanocubes and nanoflowers that expose {3 1 0} and {3 1 1} high-index facets showed a lower onset temperature for CO oxidation than Pd nanospheres of size around 6 nm. These concave nanocubes and nanoflowers were also found to catalyze the CO oxidation reaction more efficiently than simple cubes and spheres of similar size that exposed low-index facets. The enhanced activity of these nanoparticles compared with other morphologies are attributed to the presence of sites of under-coordination on the exposed high-index facets. The larger nanoparticles were also found to be more stable in the reaction environment. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: CO oxidation; High-index facets; Pd nanoparticles; structure sensitivity